DISTRIBUTION PATTERN, DENSITY AND MORPHOMETRIC CHARACTERISTICS OF SCHIZOTHORACINES (SNOW TROUTS) IN LIDDER RIVER, KASHMIR - F. A. BHAT; M. H. BALKHI; A. M. NAJAR; A. R. YOUSUF (The Bioscan, 2013)
During present study three Schizothoracines viz Schizothorax plagiostomus, S. esocinus and S. labiatus (snow trouts) were found to be inhabiting the Lidder river along with Salmo trutta fario, Crosscheilus diplochilus, Glyptosternon reticulatum and Triplophysa kashmirensis. The study was carried at three Zones (upstream, midstream and downstream) of varied topography and physical characteristics. The distributional pattern of these Schizothoracines varied at different zones though present throughout the year. S. plagiostomus was the dominant fish in the River, upstream the number of fishes of all the three Schizothorax species was low but the specimens were heavier and older and the trend was reverse downstream. Triplophysa kashmirensis and C. diplochilus were recorded only in the downstream of the River. Salmo trutta fario and G. reticulatum were present in the midstream and upstream only. The value of “n’ in Schizothoracine fishes fluctuated between 2.9467 and 3.0997. The maximum caudal fin length, head length, maximum body depth with respect to total length was observed in S. plagiostomus, S. esocinus and S. labiatus respectively. The variations in various morphometric parameters of the three species were statistically significant. Based on geographical characteristics and bio-ecological nature, the Lidder can be divided into upper trout zone and the lower carp zone.